2015
DOI: 10.1007/s40267-015-0215-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perceptions of generic medicine in Iran

Abstract: Objective The aim of this cross-sectional descriptive study was to evaluate Iranian physicians' perception of generic medicines and evaluate its relationship with their demographic characteristics, as well as some other underlying factors. Methods A self-administered questionnaire was used to evaluate the perceptions of physicians in Iran with regard to generic medicines. The questionnaire included three general questions covering physicians' beliefs and attitudes toward generic substitution, and 18 questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…33 More specifically, pharmacists can select an equivalent generic and provide proper information about the quality and safety of these products to both consumers and prescribers. 4 Consistent with other studies, the results indicated that although the majority of pharmacists are tending to inform patient about cheaper generic, 34 and willing to generic substitution, they are usually concerned about the quality, safety, and efficacy of these products, 35 while in the U.S. which has the highest rate of generic utilization, there is no evidence indicating that generic use has resulted in adverse health outcomes. 36 Even though generic medicines can be deemed as interchangeable without any concerns about safety and efficacy, as they are therapeutically equivalent with original brands, differences in such non-critical product characteristics as taste, smell, or packaging 27 can be confusing for some consumers, thereby reassuring from their physician or pharmacist would be an very effective approach.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…33 More specifically, pharmacists can select an equivalent generic and provide proper information about the quality and safety of these products to both consumers and prescribers. 4 Consistent with other studies, the results indicated that although the majority of pharmacists are tending to inform patient about cheaper generic, 34 and willing to generic substitution, they are usually concerned about the quality, safety, and efficacy of these products, 35 while in the U.S. which has the highest rate of generic utilization, there is no evidence indicating that generic use has resulted in adverse health outcomes. 36 Even though generic medicines can be deemed as interchangeable without any concerns about safety and efficacy, as they are therapeutically equivalent with original brands, differences in such non-critical product characteristics as taste, smell, or packaging 27 can be confusing for some consumers, thereby reassuring from their physician or pharmacist would be an very effective approach.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, the expenditure of pharmaceutical products has become a challenging issue for governments and patients. 3,4 For instance, a market analysis of Iranian pharmaceutical products over 13 years shows a 28.23% annual growth in value. 5 In this regard, many countries are looking for such effective strategies as generic substitution to reduce pharmaceutical costs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] It is possible, however, that some of their resistance was a related to fear of losing their dominance over a central aspect of practice [ 23,24 ] as well as perceived inadequate pharmacist knowledge. [ 25,26 ] Similarly, strong opposition to pharmacist prescribing has been reported in Kuwait, [ 27 ] Jordan, [ 28 ] Palestine [ 29 ] and Egypt. [ 30,31 ]…”
Section: Discussionmentioning
confidence: 99%
“… 37 Similar to some studies, for example, Yousefi et al , most of the physicians were dissatisfied with the pharmacists’ suggestion to generic substitutions. 38 This was mainly because some physicians believe that these activities call into their autonomy and authority or likely impair the physician–patient relationship if the pharmacist’s recommendation differs from their own. However, pharmacist-led counselling was the only activity where physicians were not directly involved in the relationship, unless they were directly informed by patients as to whether they have been counselled or otherwise.…”
Section: Discussionmentioning
confidence: 99%